Pengembangan E-Modul Dasar-dasar Listrik dan Elektronika Berbasis Problem-Based Learning - Norin Pazlina; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2020)
This research is motivated by the module used by the teacher that has not been able to stimulate students to be able to learn independently because the module used has not led students to be able to find learning concepts and the material in the module does not fully cover all the basic competencies applied in the syllabus based on the 2013 curriculum. The material presented cannot be understood by students because it is not conceptual so that students feel bored and do not have the motivation to learn. This research aims to produce a valid, practical, and effective E-Module for the Basics of Electricity and Electronics learning. This study uses a development research method with a 4D model which consists of four stages of research, namely define, design, development, and dissemination. The research subjects were students of class X TITL 1 SMK N 2 Sungai Penuh in the odd semester of the 2020/2021 school year. The research instrument was a validity questionnaire, a practicality questionnaire, and a test. The results of the research obtained E-Module validity data from material experts and media experts with a valid category. Practicality test with the teacher and student respondents obtained E-Module learning Basics of Electricity and Electronics including the very practical category. The effectiveness test of the E-Module learning Basics of Electricity and Electronics through the students' post-test results showed that the E-module was in the effective category.